Faktor Prediktif Post Dialysis Fatigue Sedang pada Pasien yang Menjalani Hemodialisis Reguler - Amu, Ivan Virnanda; Marbun, Maruhum Bonar H; Nugroho, Pringgodigdo; Rinaldi, Ikhwan; Shatri, Hamzah; Mardiana, Nunuk; Hidayat, Rudy; Susalit, Endang; Yunihastuti, Evy; Purnamasari, Dyah; Wardoyo, Elizabeth Y (Jurnal Penyakit Dalam Indonesia, 2025)
Introduction. Fatigue is often found in patients with CKD-HD. Fatigue serves as an indicator of mortality and may be a viable target in a treatment strategy. Current research has not established the determinants of moderate PDF in individuals with CKD who are undergoing HD. Therefore, this study was conducted to prove the predictor factors of moderate PDF. Methods. A retrospective cohort study in CKD-HD patients at Fatmawati Central General Hospital during the period of November-December 2024. The independent variables of this study are comorbidities, MIS, depression, intradialytic SBPV, dialysis vintage, UFG, IDWG, and anemia status. Primary data from the PDF Scale, MIS, and BDI II questionnaire were collected through patient interviews during the eighth hemodialysis session. Demographic and clinical information of the patients was obtained from medical records. Intradialytic SBPV was determined by the ARV. All variables were examined using the chi-square test, except for the depression variable, which failed to fulfil the requirements and was assessed using the Fisher exact test. A logistic regression analysis was performed to identify the most significant association among the predictor variables of moderate PDF. Results. A total of 135 research subjects were included in the study. Based on the results of the bivariate analysis, MIS, depression, and the type of dialysis were significantly linked to moderate post dialysis fatigue (p < 0.05). From the results of the multivariate analysis, inflammatory malnutrition (RR 1.580; 95% CI 1.017–2.455; p = 0.042), dialysis vintage (RR 1.850; 95% CI 1.208–2.834; p = 0.005), and depression (RR 2.165; 95% CI 1.542–3.039; p < 0.001) were obtained. The logistic regression model shows a significant relationship between moderate PDF and severe malnutrition inflammation score, mild to moderate depression, and dialysis vintage exceeding 12 months. Conclusion. Our findings underscore a significant association between depression, dialysis vintage, and malnutrition inflammation score (MIS) with moderate PDF in CKD-HD patients.